(untitled) (Sustainability in Debate, 2022)
Adaptation to climate change, understood as the moderation of sensitivities and the strengthening of adaptive capacities modifies the conditions and, consequently, the impacts of climate change on vulnerable populations. On the other hand, adaptive capacity depends on public policies tailored to different groups’ social, economic, and environmental realities. This article discusses specific vulnerabilities, adaptive measures and opportunities identified through semi structured interviews and participatory workshops in three groups with different socio-environmental profiles: the Fundo de Pasto (FP) traditional communities in Northern Bahia, the Tuxá indigenous community in Rodelas/ BA and the irrigated perimeters of the Juazeiro/BA-Petrolina/PE pole. These case studies confirm that adaptation is strongly conditioned by the physical characteristics of the region where the population is located (such as rainfall levels and proximity to perennial water bodies, which condition “risks”); but that it also depends on a wide range of social, economic, cultural, and political factors.